Mapping iron gall ink penetration within paper fibres using scanning transmission X-ray microscopy. Issue 3 (4th February 2015) - Rouchon, V.; Bernard, S.
Abstract : STXM makes it possible to map the distribution of an iron gall ink on a paper fibre cross-section. Abstract : Iron gall inks have largely been used for writing in European western countries from the Middle Ages to the twentieth century. Yet, their use may significantly damage the paper through acid hydrolysis and iron catalysed oxidation. These phenomena are not only governed by the chemistry of the ink + cellulose system, but also by the penetration of the ink within the paper sheet. Here, we investigate ink penetration at the scale of a paper fibre using synchrotron-based STXM. This technique allows in situ mapping of the iron redox state and carbon speciation down to the sub-micrometre scale. Linen fibres have been impregnated by iron sulphate, gallic acid and gum Arabic; i.e. the three main ingredients of iron gall inks. Soft X-ray transparent ultrathin foils of impregnated fibres have been extracted using FIB milling. The data reported here evidence that ink components do not penetrate through the paper fibres the same way. In the absence of gum Arabic, gallic acid penetrates within the fibre but mostly remains in the outer part of the cell wall. A significant precipitation of Fe(iii ) gallate occurs during this migration whereas small amounts of iron (mostly Fe(ii )) penetrate through the inner part of the fibre. The addition of gum Arabic as a binder makes the ink more viscous and significantly jeopardizes its ability to penetrate the fibre. The ink thus remains at the surface of the fibre. Low amounts of iron, essentially Fe(ii ), do still penetrate the fibre.